DERMATOGLYPHIC STUDY AMONG ETHNIC GROUPS OF MONGOL - D.TUMEN (Mongolian Journal of Anthropology, Archaeology and Ethnology, 2023)
Over 20 ethnic groups and tribes inhabit the territory of Mongolia. Linguistically the ethnic groups and tribes are divided into two subdivisions of Altaic linguistic family (Turkic and Mongolian subdivisions). We investigated 7200 dermatoglyphic samples from 24 ethnic groups and tribes and compared the results with those found in other Asian populations using dermatoglyphic traits (PII, MLI, t, Hy, AIT). The geographic variations of the dermatoglyphic traits show three distinct patterns of variation. The first is a general W-E pattern - increasing from West to East for PII and t, and trend in the opposite direction for MLI. The second pattern is the patch variation observed for Th/1 and AIT. The lowest and highest frequencies are found in the West as well as in the East. The third pattern is from North to East and South, decreasing for Hy. The comparison shows a presence of two dermatoglyphic variants in Mongolia. One of those variants is characterized by the moderate expression of “Mongoloid” dermatoglyphic features. All turkic speaking ethnic groups and some of Mongolian speaking groups from Western Mongolia belong to this variant. The typical maximum “Mongoloid” dermatoglyphic features (highest value of PII and t) characterize the second variant. All ethnic groups and tribes from Southeast Mongolia belong to this variant.